VISÃO DA POPULAÇÃO DOS MUNICÍPIOS DE SÃO PAULO (BRASIL) e MEDELLÍN (COLÔMBIA) ACERCA DOS EFEITOS SOCIOECONÔMICOS CAUSADOS PELA PANDEMIA DO NOVO CORONAVÍRUS (Gestão & Regionalidade, 2024)
COVID-19 affected the habits of populations: work, study, mobility, and interpersonal relationships and highlighted social differences, hitherto ignored. In general, governments have been taking actions to combat the pandemic and mitigate the speed of contamination. However, in many cases, these actions have been shown to be disconnected from the population. Within this context, this article aims to demonstrate the view of the inhabitants of São Paulo and Medellín about the effectiveness of actions carried out by municipal governments to identify situations in common and contrasts. To this end, a multiple case study was conducted in which citizens were interviewed. Then, the interviews were transcribed and analyzed. The vision of the population impacted by the pandemic is essential for evaluating public policies in progress and for the planning of actions to guarantee the resilience of cities concerning the established crisis.
Keywords: Covid 19.; urban planning; urban resilience; collective health